Neural Structures Associated with Music Engagement in Persons with Alzheimer’s Disease - Zaitsev, Pavel (My University, 2020)
Alzheimer’s disease (AD) is the most common cause of dementia and a major public health issue resulting in decreased life expectancy of patients and high societal cost. Medical treatment of AD is palliative in nature as there is no definite cure. The symptoms can be alleviated through psychosocial interventions such as music-based rehabilitation. The aims of this small-scale study were to examine how AD affects the structure of brain areas associated with music engagement. Recently diagnosed patients with AD (N=5) were interviewed using Music Engagement Questionnaire (MusEQ) to acquire behavioral data relating to their musical activities. Using structural Magnetic Resonance Imaging (MRI) data acquired prior to this study with clinical indication, correlational Voxel-Based Morphometry (VBM) analyses were carried out evaluating the relationship between the neural architectures and MusEQ subtests and total score. Greater MusEQ total scores were associated with greater grey matter volume (GMV) in parietal and superior occipital areas, bilaterally. Greater GMV in frontal, limbic and inferior occipital areas were associated with higher scored both in Daily and Respond subtests. Higher scores in Emotion subtest were associated with greater GMV in the left parietal areas. The current results of the present feasibility-type study provide putative evidence on the relationship between music engagement and brain plasticity in persons with AD, and, if verified in a larger patient population, could contribute to personalized implementation of music-based therapeutic approaches for patients with memory impairment.
Keywords: Alzheimer’s disease, Grey matter volume, Magnetic Resonance Imaging, Voxel-Based Morphometry, Music Engagement Questionnaire